Parental Post-traumatic Stress Disorder Symptoms Are Related to Successful Aging in Offspring of Holocaust Survivors - Shrira, Amit; Ayalon, Liat; Bensimon, Moshe; Bodner, Ehud; Rosenbloom, Tova; Yadid, Gal (Frontiers in Psychology, 2017)
A fascinating, yet underexplored, question is whether traumatic events experienced by previous generations affect the aging process of subsequent generations. This question is especially relevant for offspring of Holocaust survivors (OHS), who begin to face the aging process. Some preliminary findings point to greater physical dysfunction among middle-aged OHS, yet the mechanisms behind this dysfunction need further clarification. Therefore, the current studies assess aging OHS using the broad-scoped conceptualization of successful aging, while examining whether offspring successful aging relates to parental posttraumatic stress disorder (PTSD) symptoms and offspring's secondary traumatization symptoms. In Study 1, 101 adult offspring (mean age = 62.31) completed measures of parental PTSD, secondary traumatization, as well as successful aging indices – objective (medical conditions, disability and somatic symptoms) and subjective (perceptions of one's aging). Relative to comparisons and OHS who reported that none of their parents suffered from probable PTSD, OHS who reported that their parents suffered from probable PTSD had lower scores in objective and subjective measures of successful aging. Mediation analyses showed that higher level of secondary traumatization mediated the relationship between parental PTSD and less successful aging in the offspring. Study 2 included 154 dyads of parents (mean age = 81.86) and their adult offspring (mean age = 54.48). Parents reported PTSD symptoms and offspring reported secondary traumatization and completed measures of objective successful aging. Relative to comparisons, OHS whose parent had probable PTSD have aged less successfully. Once again, offspring secondary traumatization mediated the effect. The findings suggest that parental posttraumatic reactions assessed both by offspring (Study 1) and by parents themselves (Study 2) take part in shaping the aging of the subsequent generation via reactions of secondary traumatization in the offspring. The studies also provide initial evidence that these processes can transpire even when offspring do not have probable PTSD or when controlling offspring anxiety symptoms. Our findings allude to additional behavioral and epigenetic processes that are potentially involved in the effect of parental PTSD on offspring aging, and further imply the need to develop interdisciplinary interventions aiming at promoting successful aging among offspring of traumatized parents.